Understanding CO2 decomposition in microwave plasma by means of optical diagnostics. Issue 6 (24th October 2016) - Silva, Tiago; Britun, Nikolay; Godfroid, Thomas; Snyders, Rony
Abstract : The growing interest to plasma‐based greenhouse gas decomposition requires the knowledge of the different kinetic mechanisms inherent in CO2 discharges and post‐discharges. This automatically involves extensive plasma diagnostics research work. Among different types of plasma diagnostics, the ones based on optical spectroscopy are of particular relevance due to their non‐intrusiveness. The recent progress in optical diagnostics of plasma‐assisted CO2 decomposition process is discussed in this work. A microwave surfaguide discharge operating at 2.45 GHz in several CO2 ‐containing mixtures was investigated. Optical emission spectroscopy is used to characterize the discharge area of the reactor in terms of fundamental plasma parameters. At the same time, two‐photon absorption laser‐induced fluorescence is applied for investigation of oxygen and carbon monoxide concentrations in the post‐discharge. Abstract : In this work, a microwave surfaguide discharge operating at 2.45 GHz in several CO2 ‐containing mixtures is investigated. Among various useful applications, these sources are considered to be energy‐efficient and powerful plasma‐chemical systems in gas reforming. This subject is highly important nowadays due to the growing interest to plasma‐based CO2 decomposition. We used optical emission spectroscopy and two‐photon absorption laser‐induced fluorescence to study plasma‐assisted CO2 conversion in relation with plasma parameters, such as electron and gas temperature, etc. The current paper is targeted to demonstrate a potential for optimization of the pulsed microwave discharges for increasing the CO2 decomposition efficiency as well as to show an importance of the optical diagnostic methods for characterization of various physical and chemical mechanisms related to CO2 plasmas.